PENGARUH JENIS MEDIA TANAM DAN PUPUK URINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCHOY (Brassica rapa L.) - Pradana, Kharisma Enggar; Soemarah K.D, Tyas; Suprapti, Endang; Wiyono, Wiyono; Sari, Siti Mardhika (Universitas Islam Kadiri, 2026)
This study aimed to evaluate the effects of planting media composition and the concentration of liquid organic fertilizer derived from cow urine on the growth and yield of pakchoy (Brassica rapa L.). The research was conducted from November to December 2025 at the TPH Tohudan Seed Garden, Klipan, Tohudan, Colomadu District, Karanganyar Regency, at an altitude of approximately 150 m above sea level, using a factorial Completely Randomized Design (CRD) with two factors. The first factor was planting media composition, consisting of soil; soil + rice husk charcoal (1:1); soil + compost (1:1); and soil + rice husk charcoal + compost (1:1:1). The second factor was the concentration of liquid organic fertilizer from cow urine, namely 0, 50, 100, and 150 mL L⁻¹ of water. The results showed that the planting media composed of soil + rice husk charcoal + compost (1:1:1) produced the best growth and yield of pakchoy, the optimal concentration of liquid organic fertilizer from cow urine was 100 mL L⁻¹ of water, and the combination of planting media and liquid organic fertilizer application had a significant effect on the growth and yield of pakchoy.. Keyword : pakchoy, concentration, fertilizer form, organic fertilizer, planting media